The value and role of cemeteries: Designing a possible methodology for teaching heritage to history learners (Yesterday & Today Journal for History Education in South Africa and abroad, 2010)
Teaching heritage to History learners is imperative as an aid to help them discover their uniqueness but also their commonalities. A sense of heritage does not only contribute to a feeling of belonging and identity, but also promotes social cohesion, mutual understanding and unity in a multi-cultural, multi-national country. Due to its perceived value, heritage as a theme is recognised as one of the knowledge focuses for History as prescribed in the National Curriculum Statement. However, for various reasons, heritage does not receive the attention in the teaching and learning of History it deserves. By concentrating on the value and role of cemeteries, the purpose of this article is to provide History teachers with a step-by-step methodology in support of the effective teaching of heritage.
Keywords: History teaching and learning; Heritage; Cemeteries; History methodology; History education